INFLUENCE OF FINANCIAL TECHNOLOGY (FINTECH) ON FINANCIAL INDUSTRY - Musabegović, Ismmail; Özer, Mustafa; Đuković, Slađana; Jovanović, Stefan (Economics of Agriculture, 2019)
The financial technology (hereinafter: fintech) industry is growing rapidly which is supported by the fact that it received more than $20 billion in investment last year alone. This article surveys historical development of fintech and its influence on market structure in banking industry, efficiency, strategic plans of participants, and stability of financial market. Based on World Bank database, the paper tests the fundamental premise – whether there is a relationship between country GDP and population and usage of new technology and smartphones in financial transactions and payment processing. The results of the study provide evidences of statistically significant positive relationships between per capita GDP and usage of new technology and smartphones in financial transactions and payment processing. Also, they indicate statistically significant positive relationships between per capita GDP and payment of utilities and received wages through a mobile phone. Thus, the results of study should be taken into consideration when forming the policies regarding the use of new technology and smartphones in financial transactions and payment processing.